Pantun Melayu: Kajian Terhadap Pesan Dakwah Dalam Tafsir al-Azhar - Kusnadi Kusnadi (Wardah, 2016)
Abstract: al-Azhar tafsir is among tafsir in Indonesian have used poems in explanation of some verses of the Koran. This work have been Hamka done to present means and some message of verse. That poem is result of Malay community culture and used to express feelings of happines, sadness, and consolation. Some of the poems used describe the feeling of the soul, parables, and advice. This article is aimed to analyzing messages of dakwa in some poems at tafsir al-Azhar. It is found that some poems as a result of inspiration of life, parable, and a reflection of Malay community culture.